Model of Problem Based Learning Assisted with Multimedia Flash in Improving the Concept Understanding of Elementary School Students (Universitas Negeri Semarang, 2019)
This study has purpose to determine the difference of the improvement of concept understanding in the problem based learning model assisted with flash multimedia with direct instruction model. The research method used in this study was quantitative of research using pretest-posttest design. This study was conducted at an Elementary School in Brebes Regency in science learning of single and mixed substances in grade V. The sample in this study were 38 students taken for experimental class and 32 students for control class. The data collection techniques used were observation and test. The data analysis techniques used to gain the significant difference was t-test. The results of this study indicated that the ability of concepts understanding of students in the problem based learning model assisted with flash multimedia is better than that of the direct instruction learning model. The independent sample t-test with a significance of 0.015 < 0.05. The average value obtained by the experimental class with a score of 79.95 and the average value of the control class with a score of 75. Therefore, it can be concluded that the use of problem based learning model assisted with flash multimedia can improve the ability of concepts understanding of students.